2022
DOI: 10.1175/wcas-d-21-0034.1
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Probability Information in Weather Forecasts: Findings and Recommendations from a Living Systematic Review of the Research Literature

Abstract: Probabilistic forecast information is rapidly spreading in the weather enterprise. Many scientists agree that this is a positive development, but incorporating probability information into risk communication can be challenging because communicators have little guidance about the most effective way to present it. This project endeavors to create such guidance by initiating a “living systematic review” of research studies that empirically examine the impact of risk messages that use probability information on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 171 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…This finding concludes that an objective measure like PoP can be subjectively interpreted (or misinterpreted), indicating that the vast efforts exploring the communication and interpretation of probabilistic information should continue (Ripberger et al, 2022), potentially even focusing on best practices for communicating probabilistic information on weather apps. Understanding interpretation by the public is vital to having appropriate messaging that avoids communicating inaccurate expectations.…”
Section: Discussionmentioning
confidence: 97%
“…This finding concludes that an objective measure like PoP can be subjectively interpreted (or misinterpreted), indicating that the vast efforts exploring the communication and interpretation of probabilistic information should continue (Ripberger et al, 2022), potentially even focusing on best practices for communicating probabilistic information on weather apps. Understanding interpretation by the public is vital to having appropriate messaging that avoids communicating inaccurate expectations.…”
Section: Discussionmentioning
confidence: 97%
“…However, as these participants were only provided with the warning color for their region, this may be due to the absence of information on likelihood and severity. Nonetheless, other studies examining perceptions of likelihood and severity have found that when warned for events are more severe they tend to be perceived as more likely to occur (see Ripberger et al, 2022;Weber & Hilton, 1990).…”
Section: Probability and Judgments About Weather Riskmentioning
confidence: 99%
“…Finding ways to communicate uncertainty in different weather products has been a priority of the weather enterprise for over a decade [95][96][97][98][99]. The 3A and 4E approaches involve different kinds of uncertainty depending on present or future timeframes.…”
Section: Uncertaintymentioning
confidence: 99%